2013
DOI: 10.1038/npp.2013.44
|View full text |Cite
|
Sign up to set email alerts
|

Baseline-Dependent Effects of Cocaine Pre-Exposure on Impulsivity and D2/3 Receptor Availability in the Rat Striatum: Possible Relevance to the Attention-Deficit Hyperactivity Syndrome

Abstract: We have previously shown that impulsivity in rats predicts the emergence of compulsive cocaine seeking and taking, and is coupled to decreased D2/3 receptor availability in the ventral striatum. As withdrawal from cocaine normalises high impulsivity in rats, we investigated, using positron emission tomography (PET), the effects of response-contingent cocaine administration on D2/3 receptor availability in the striatum. Rats were screened for impulsive behavior on the five-choice serial reaction time task. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 59 publications
5
39
2
Order By: Relevance
“…Furthermore, it is a well-established vulnerability marker for the development of substance use disorders (Verdejo-García, Lawrence & Clark 2008), as has also been demonstrated in preclinical research (Belin et al 2008). Of particular relevance for the current study, trait impulsivity in rats interacts with acute cocaine effects on response inhibition, such that highly impulsive rats show the strongest benefit to response inhibition from cocaine (Dalley et al 2007;Winstanley et al 2009;Caprioli et al 2013). Likewise, trait sensation or novelty seeking is associated with a younger age at which people first use cannabis and cocaine (Jaffe & Archer 1987;Martin et al 2002).…”
Section: Introductionmentioning
confidence: 63%
“…Furthermore, it is a well-established vulnerability marker for the development of substance use disorders (Verdejo-García, Lawrence & Clark 2008), as has also been demonstrated in preclinical research (Belin et al 2008). Of particular relevance for the current study, trait impulsivity in rats interacts with acute cocaine effects on response inhibition, such that highly impulsive rats show the strongest benefit to response inhibition from cocaine (Dalley et al 2007;Winstanley et al 2009;Caprioli et al 2013). Likewise, trait sensation or novelty seeking is associated with a younger age at which people first use cannabis and cocaine (Jaffe & Archer 1987;Martin et al 2002).…”
Section: Introductionmentioning
confidence: 63%
“…This observation therefore suggests that the potential delay in dorsal striatal recruitment after cocaine exposure observed in HI rats might be attributed to cocaine-induced remediation of low D2 dopamine receptors in the ventral striatum and the associated impulsivity that occurs early on after cocaine self-administration. Indeed, this hypothesis is supported by a recent micro positron emission topography study in LI and HI rats (46). This has important implications at the psychological level in that it suggests that, for HI rats, instrumental actions for cocaine might remain goal-directed for longer than in LI rats, a consequence partly determined by a dopamine deficiency state in the ventral striatum.…”
Section: Discussionmentioning
confidence: 78%
“…In particular, exposure to drugs of abuse has been reported to produce an enhancement in impulsive-like responding in animals (Dallery and Locey, 2005; Richards et al, 1999) and in humans (de Wit, 2009). Although there are evidence that drug exposure could reduce some forms of impulsivity (Caprioli et al, 2013), animal studies aimed at identifying vulnerability factors for the development of addiction consistently reveal that impulsivity itself may influence the development of drug dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, impulsivity in animals correlates with reduced D 2 receptor availability in the striatum. Using PET and autoradiography, previous studies have shown that D 2 receptor availability is reduced in the nucleus accumbens of impulsive rats (Dalley et al, 2007; Jupp et al, 2013; Caprioli et al, 2013). In monkeys, D 2 receptor availability is inversely correlated with impulsive responses (Czoty et al, 2010).…”
Section: Introductionmentioning
confidence: 99%